"Fake prey": planktonic ostracods negatively affect the predatory performance of Chaoborus larvae. (21st November 2017) - Maroneze, Daniel M; Pujoni, Diego G F; Maia-Barbosa, Paulina M
Abstract: Previous laboratory experiments have indicated that Chaoborus larvae may be confused when exposed to a single prey species at a high density, resulting in decreased attack efficiency. Here, we hypothesized that a prey less vulnerable to Chaoborus larvae, such as Physocypria schubarti ostracods, could affect the predatory performance of Chaoborus on a more vulnerable prey, such as Ceriodaphnia silvestrii neonates. We predicted that fewer neonates would be ingested by Chaoborus larvae in the presence of ostracods at high densities due to the decreased attack efficiency caused by the confusion effect. This hypothesis was tested by combining predation assays and direct visual observations of live organisms. There was a significant decrease in the consumption of neonates when they were offered together with ostracods at high densities; however, this was not related to the ingestion of ostracods as an alternative prey or to decreased attack efficiency on neonates caused by the confusion. The energy wasted due to the numerous attacks on the ostracods ("fake prey") possibly led the chaoborids to exhaustion, reducing their predatory performance on neonates. In ecological terms, high densities of ostracods in the water column may theoretically minimize the strong impact of Chaoborus sp. larvae on more vulnerable prey.